CLAY CONSTRUCTION COMPOSITES BASED ON CHEMICALLY ACTIVATED RAW MATERIALS AND ORGANIC CONNECTORS - Yu. G. Ivaschenko; R. T. Mameshov; K. K. Mukhambetkaliev (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim of this work is to study the theoretical aspects and technological possibilities of chemical activation and modification of organic clay raw materials of the Volga region in organic additives to obtain composite building materials based on previous work on the development of clay cement composites.Method. In connection with the high physicochemical activity of clay and cement with respect to organic additives and mineral salts, expressed in the high adsorption activity and sensitivity of hydration processes, studies of the structure of clay were studied separately from cement. To determine the change in pH value of suspensions from clay and clay cement raw materials, the role of the influence of ECA products of treatment of aqueous-salt solutions of sodium chloride and ACF resin was studied.Result. The results of the tests showed that by changing the pH values of the clay cement samples by the products of electrochemical activation of water-salt solutions, it is possible to actively influence the active centers of the surface of clay particles. The adsorption and capacity of the cation exchange of clay raw materials are reduced when they are modified with acetone formaldehyde resin.Conclusion. The studies carried out to study the structure formation and the nature of the effect of the pH of the system environment on the process of the condensation of the ACF resin create the prerequisites for further research in the field of soil consolidation, their stabilization and enhance-ment of operational parameters.